Synthesis of 2-Aminooxazolines and Spiro-2-aminooxazolines by Using a Convenient Two-Step INCO-Mediated Reaction - Anderson, Corey D.; Wilson, Dean M.; Mao, Long; Ramirez-Weinhouse, Michele; Long, Daniel D.; Crane, Christine M.; Jolivet, Catherine; Fanning, Dewey; Molteni, Valentina; Termin, Andreas (Synlett, 2013)
A two-step reaction sequence yielding 2-aminooxazolines under mild conditions was developed. Both electron-rich and electron-deficient styrenes as well as functionalized primary and secondary amides could be used in the reaction to afford 2-aminooxazolines in reasonable yields.
Keywords: isocyanate; library generation; styrene; heterocycles; multicomponent reactions